Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1038/sj.onc.1207405
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations in spontaneous and carcinogen-induced murine melanoma cell lines

Abstract: We have conducted an analysis of genetic alterations in spontaneous murine melanoma cell line B16F 0 and its two metastatic clones, B16F 1 and B16F 10 and the carcinogeninduced murine melanoma cell lines CM519, CM3205, and K1735. We found that unlike human melanomas, the murine melanoma cell lines did not have activating mutations in the Braf oncogene at exon 11 or 15. However, there were distinct patterns of alterations in the ras, Ink4a/Arf, and p53 genes in the two melanoma groups. In the spontaneous B16 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 78 publications
4
78
1
Order By: Relevance
“…Here, we also showed that vincristine could transcriptionally regulate the mTUBB2 gene. Furthermore, although genomic alteration of the p53 gene in B16F10 cells has been reported, several studies have indicated that the p53 in these cells seems to be functional (41,42). Our results also showed that p53 protein in B16F10 cells at least retained its binding activity to the response element.…”
Section: Discussionsupporting
confidence: 74%
“…Here, we also showed that vincristine could transcriptionally regulate the mTUBB2 gene. Furthermore, although genomic alteration of the p53 gene in B16F10 cells has been reported, several studies have indicated that the p53 in these cells seems to be functional (41,42). Our results also showed that p53 protein in B16F10 cells at least retained its binding activity to the response element.…”
Section: Discussionsupporting
confidence: 74%
“…2). This synergy was most powerfully corroborated in mouse transgenic models in which pairwise activation and inacti vation of NRAS and CDKN2A, BRAF and PTEN, or BRAF and CDKN2A, respectively, gave rise to melanoma with high fidelity 14,15 . Characterization of tumours from large cohorts of patients with advanced-stage melanoma at the whole-genome level has provided greater granularity regarding the overall prevalence of these genetic alterations, as well as their overlap 5,9,16 (FIG.…”
Section: Genetic and Immune Landscape Of Melanomamentioning
confidence: 84%
“…Here, we investigated the involvement of CKIs in G 1 cell-cycle arrest, and found that p27Kip1, but not p21Cip1, accumulated in B16 tumor cells following CTL therapy in vivo or IFNg treatment in vitro. Another CKI, p16, is involved in senescence-like G 1 cell-cycle arrest (14), but this factor is not expressed in B16 tumor cells due to a p16 Ink4a exon1a deletion (34). Thus, p27Kip1 appeared to be the major CKI involved in G 1 arrest in this model.…”
Section: Discussionmentioning
confidence: 97%